IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM REKRUITMEN DENGAN SISTEM COMPUTER ASSISTED TEST - Yasin, Reza (Jurnal Ilmu Administrasi Negara, 2016)
This study aims to determine the implementation of the recruitment policy of the system Computer Assisted Test (CAT). Factors influencing the XII Regional Office of State Personnel Board Pekanbaru. Key informant was a member of the executive committee of the examinees. Data collecting technique is interview, observation and documentation. Analysis of data using an interactive model. The results showed government policy implementation Computer Assisted Test (CAT) in the Regional Office of State Personnel Board XII Pekanbaru has been implemented well. It is influenced by the process smooth communication between all parties and human resources are very good in terms of quality.